Colchicine in Post-operative Atrial Fibrillation: A Review - Vrachatis, Dimitrios A.; Kossyvakis, Charalampos; Angelidis, Christos; Panagopoulou, Vasiliki; Sarri, Eleni K.; Giotaki, Sotiria; Siasos, Gerasimos; Vavuranakis, Manolis; Deftereos, Spyridon G. (Current Pharmaceutical Design, 2018)
Post-operative atrial fibrillation (POAF) is a frequent entity increasing hospitalization duration, stroke and mortality. In the recent years, a few studies have sought to investigate the potential effect of colchicine in POAF prevention after cardiac surgery or catheter pulmonary vein isolation for AF. In the present review article, we intend to provide a synopsis of clinical practice guidelines, summarize and critically approach current evidence for or against colchicine as a means of POAF prevention.
Keywords: AFib